2016
DOI: 10.1080/14763141.2016.1212916
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the risk and biomechanical consequences of lateral epicondylalgia by estimating wrist and finger muscle capacities in tennis players

Abstract: Previous studies suggested that a pronounced weakness of the extensor muscles relative to the flexor muscles could increase the risk of occurrence of lateral epicondylalgia. This study investigates this hypothesis by estimating the ratio of extensor to flexor muscle capacities among healthy non-players (n = 10), healthy tennis players (n = 20), symptomatic players (n = 6), and players who have recovered from lateral epicondylalgia (n = 6). Maximum net joint moments in flexion or extension were measured during … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
(62 reference statements)
0
6
0
Order By: Relevance
“…This study provided a model of the force-length behaviour of the ECR and EDC muscles capacities represent a risk factor for lateral epicondylalgia [37], these relationships could help to design tool handles and recommendations for manual tasks such that extensor muscles remain close to their optimal length when they are highly involved. By describing how muscle capacities are affected by joint posture, the models obtained in the present study could also be used to clarify how biomechanical constraints might influence the muscle coordination during grasping tasks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study provided a model of the force-length behaviour of the ECR and EDC muscles capacities represent a risk factor for lateral epicondylalgia [37], these relationships could help to design tool handles and recommendations for manual tasks such that extensor muscles remain close to their optimal length when they are highly involved. By describing how muscle capacities are affected by joint posture, the models obtained in the present study could also be used to clarify how biomechanical constraints might influence the muscle coordination during grasping tasks.…”
Section: Resultsmentioning
confidence: 99%
“…sewing or hammering, and the muscle coordination varies according to the task constraints [3]. Considering the balance of muscle capacities between flexors and extensors 9 can influence the muscle coordination and might represent a risk factor in lateral epicondylalgia [37], providing a framework to analyse the force-generating capacities of those muscle groups appears necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the musculo-skeletal model relied on generic muscle capacities, for example, PCSA, whereas studies showed that tennis playing modifies the hand musculature nonuniformly across hand flexors and extensors. 24 The obtained muscle load sharing could have thus been modified if the musculo-skeletal model included player-specific capacities. Nevertheless, obtaining this player-specific muscle strength profile would have required another measurement session, whereas the protocol already lasted 2 h and a half on average.…”
Section: Limitationsmentioning
confidence: 99%
“…12,23 Those studies showed that both flexion-extension (FE) and radialulnar deviation (RUD) are facing high torques with values around 5-15 Nm and reaching sometimes 30 Nm, thus similar to maximal isometric contraction performances. 24 Authors also showed that the distribution of the wrist torque between the two degrees of freedom can vary importantly according to the player's individual technique, with for instance larger RUD torques in professional players and larger FE torques in intermediate ones. 23 Although the net moment traduces the overall mechanical demand at the joint, it does not allow to characterize how forces are shared across individual muscles.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation